Habitat Utilization by Indian Peafowl, Pavo cristatus (Phasianidae), in Indroda Nature Park, Gandhinagar, Gujarat, India - Munjpara, Sandeep; Bhavsar, Happy; Kamboj, R. D. (Indian Forester, 2020)
The behavioural activities of the Indian Peafowl (Pavo cristatus) from the various environments oflndroda Nature Park (INP), Gandhinagar, Gujarat was evaluated based on the Activity Budget method. It was inferred that Indian Peafowl utilize the INP for all m ajorbehavioural activities. However, maximum time was spent for foraging activity followed by resting activity. The study has also brought out that Botanical Garden and Campsite of lNP were utilized for all requisites. These areas were observed to be suitable forresting as they are covered with tall trees.